Parathyroid hormone-related protein as a tumour marker in humoral hypercalcaemia associated with occult malignancy. Issue 814 (August 1993) - Hutchesson, A. C.; Dunne, F.; Bundred, N. J.; Gee, H.; Ratcliffe, W. A.
Abstract : The tumour-derived factor PTH-related protein (PTHRP) is the primary humoral factor responsible for hypercalcaemia in patients with solid tumours. In a woman presenting with anaemia and hypercalcaemia, the finding of raised plasma PTHRP and undetectable serum PTH concentrations led to further investigations and the subsequent identification of a uterine tumour. No evidence of tumour spread was found at operation, and removal of the tumour resulted in normalization of both serum calcium and plasma PTHRP. Expression of PTHRP by the tumour was shown by immunohistochemistry and in situ hybridization. We conclude that the identification of an occult tumour in a patient with hypercalcaemia and raised plasma PTHRP provides evidence of the diagnostic utility of PTHRP immunoassays in the investigation of patients with hypercalcaemia and suspected malignancy.